2005
DOI: 10.1148/radiol.2363041262
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Findings in Autoimmune Hepatitis: Correlation with Clinical Staging

Abstract: Although fibrosis is a common feature in AIH and is often moderate to severe, no significant correlation between fibrosis grade and MELD score was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…Conversely, the negative findings on MRCP might not completely exclude early-stage SC, because MRCP is considered by some authors of lower sensitivity than ERCP for the diagnosis of proximal bile duct lesions, even if this has not been clearly demonstrated in the field of PSC. 25,26 Bilaj et al 27 have recently documented the MRI appearance of AIH, and this report is consistent with our data. The authors observed mild IHBD dilatation in 12% of AIH patients (4/32 patients).…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the negative findings on MRCP might not completely exclude early-stage SC, because MRCP is considered by some authors of lower sensitivity than ERCP for the diagnosis of proximal bile duct lesions, even if this has not been clearly demonstrated in the field of PSC. 25,26 Bilaj et al 27 have recently documented the MRI appearance of AIH, and this report is consistent with our data. The authors observed mild IHBD dilatation in 12% of AIH patients (4/32 patients).…”
Section: Discussionsupporting
confidence: 93%
“…The characteristic imaging findings of fibrosis depending on the etiology of cirrhosis are also seen; for example, AIH shows mostly extensive reticular and/or confluent fibrosis [31], PBC frequently shows lace-like pattern fibrosis [32], and alcoholic cirrhosis occasionally shows confluent fibrosis [4] also demonstrated in this study. The distinct amount of histological fibrosis promoted by metabolic production of alcohol in alcoholic cirrhosis [33] may have some relation with the difference in the appearance of fibrosis.…”
Section: Discussionsupporting
confidence: 67%
“…25 These characteristic histological findings of fibrosis, depending on the aetiology of cirrhosis, can be depicted by imaging. [26][27][28] Furthermore, progressive hepatic fibrosis evokes the so-called regenerative nodules in cirrhosis. 29 Cirrhosis is classified as macronodular, micronodular and mixed nodular based on the size of regenerative nodules, with this also tending to depend on aetiology.…”
Section: Discussionmentioning
confidence: 99%